2016
DOI: 10.1080/14787210.2016.1193435
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing for acute bronchitis

Abstract: Antibiotics for acute bronchitis have been associated with an approximately half-day reduction in duration of cough. However, at follow-up there are no significant differences in overall clinical improvement inpatients treated with antibiotics compared with those receiving placebo. Despite this, antibiotics are administered to approximately two thirds of these patients. This review discusses the reason for this antibiotic overprescription. Other therapies targeted to control symptoms have also demonstrated a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Reasons for the poor compliance may be related to concerns about maintaining the doctor-patient relationship, patient expectations, and the fact that general practitioners are 'just used to prescribing antibiotics' , [3] as found in other settings. There is therefore a need for practitioners to discuss the nature of the condition, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reasons for the poor compliance may be related to concerns about maintaining the doctor-patient relationship, patient expectations, and the fact that general practitioners are 'just used to prescribing antibiotics' , [3] as found in other settings. There is therefore a need for practitioners to discuss the nature of the condition, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] While national and international guidelines for treating acute bronchitis do not recommend the use of antibiotics, [4,6,7,11,12] more than 50% of patients are prescribed one. [3] A study summarising multistage RESEARCH probability surveys of ambulatory care in the USA reported a prescription rate of 71% between 1996 and 2010, from 60 -80% between 1980 and 1999. [9] A study in The Netherlands focusing on children reported a prescription rate of 46% for a diagnosis of acute bronchitis.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady improvement of symptoms over time in the placebo group is a well-known phenomenon corroborating the self-limiting nature of the disease: In all the placebo-controlled studies on effects of medications, the BSS total score under placebo decreased significantly from the first to the final visit [35]. However, most patients suffering from acute bronchitis still seek medical advice due to persisting cough and substantial symptomatic discomfort [2,4,8,36]. Investigations on the appropriate treatment of cough revealed that the patients' pressure and expectations lead a majority of physicians to the unnecessary prescription of antibiotics [8,37] although several guidelines and meta-analyses have found no benefit in the use of antibiotics for the treatment of acute bronchitis [3,5,8,9,14,38,39].…”
Section: Ear and Labyrinth Disordersmentioning
confidence: 92%
“…Nevertheless, up to 90% of episodes of acute respiratory illness in otherwise healthy individuals are considered to be of viral origin [1,3,[7][8][9]. Accordingly, the diagnosis of acute bronchitis is based on clinical symptoms and aims to rule out serious conditions (e. g. asthma) and severe bacterial infections, especially pneumonia.…”
Section: Original Articlementioning
confidence: 99%